Expert System of Early Detection of Arthritis with Web-Based Certainte Fector Method: Expert System of Early Detection of Arthritis with Web-Based Certainte Fector Method - Muhamad Alfaiz; Iskandar Fitri; Novi Dian Nathasia (Institute of Computer Science (IOCS), 2020)
Rheumatoid disease is one type of disease that attacks the joints in humans. Patients with this disease if it does not know the type of type of arthritis can cause paralysis. Expert systems in this study is expected to be one of the solutions for the early detection of arthritis in the joints of man. The method used is Certainty Factor, this method can cope with uncertainty in decision-making based on perceived symptoms that have been fed by the user. The purpose of this research is done by means of a comparison between the method of certainty factor with Dempster Shafer, so as to approach the best accuracy value. This expert system is created using the programming language PHP and MySQL database, Created by a web-based system which is expected to facilitate the user in getting information about Arthritis disease. The test results from this journal by comparing the certainty factor method with Dempster Shafer method. The result is the method of Dempster Shafer gain accuracy value of 96% of 50 test data, and the certainty factor method gain accuracy rate of 98% of 50 test data.